2017
DOI: 10.11648/j.ijnrem.20170205.11
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Monitoring of Bush Encroachment by <i>Euclea divinorum</i> in Ol Pejeta Conservancy Laikipia, Kenya

Abstract: Abstract:Bush encroachment refers to the invasion of woody species in Savannah ecosystems driven by either anthropogenic and/or natural factors. This study sought to examine land cover changes and topographic features attributable to patterns of encroachment in Ol Pejeta Conservancy (OPC) where, Euclea divinorum unpalatable woody species has colonised former grasslands and other habitats which provide grazing grounds for herbivore wildlife species. Here, we monitored vegetation cover trends in the period 1987-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Although these studies have broadened the understanding and scope of the bush encroachment phenomenon, from its impact on the ecology to its impact on carbon sequestration (Stafford et al, 2017), there has been no correlation between bush encroachment and climate variability in rangeland areas, especially by using remotely-sensed data. However, some studies have used remote sensing to compare the biodiversity between the protected savannah rangeland and the adjacent non-protected farmland in the southern Kalahari (Munyati et al, 2011;Mutunga, 2018). There are some gaps that still need to be explored with regard to the impact of climate variability on rangeland bush encroachment, especially in southern Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies have broadened the understanding and scope of the bush encroachment phenomenon, from its impact on the ecology to its impact on carbon sequestration (Stafford et al, 2017), there has been no correlation between bush encroachment and climate variability in rangeland areas, especially by using remotely-sensed data. However, some studies have used remote sensing to compare the biodiversity between the protected savannah rangeland and the adjacent non-protected farmland in the southern Kalahari (Munyati et al, 2011;Mutunga, 2018). There are some gaps that still need to be explored with regard to the impact of climate variability on rangeland bush encroachment, especially in southern Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Given the observed trends in precipitation seasonality, droughts and land use in East African countries, this is expected to change in the future; therefore, monitoring techniques, such as the deployment of hyperspectral and multispectral sensors, are used to improve our understanding of the potential impacts of land-use changes on the ecosystem services in the East African rangelands. It has been observed that Kenya has a high rate (39%) of bush encroachment in the rangeland areas, with the severe impact being felt in both the protected and unprotected areas, which changes the livestock grazing habits and conservation benefits (Mutunga, 2017(Mutunga, , 2018.…”
Section: Discussionmentioning
confidence: 99%